The use of expressions in character speech and their relation to psycholinguistics - Buronova Rano Abdujabborovna; Uralova Aziza Dilmurod qizi (Peerian Journals Publishing, 2022)
The role of phrases in the integration of the idea expressed in the character's speech The units of language that exist as an opportunity in the memory of individual speakers are called stable compounds. These stable units define speech. Enrich the language of the work. The most common of these units is the phraseological unit-phrase, which enriches the language of the work. Provides emotional-expressive coloring.
Keywords: Emotional-expressive; Speech process; Stable connection; speech sensitivity